Pengaruh Model Pembelajaran dan Kecerdasan Intelektual Terhadap Hasil Belajar Sejarah Siswa di SMA Negeri 1 Karawang - Megawati, Indah (Jurnal Pendidikan Sejarah, 2017)
This research is purpose to find the influence of instructional model and intellegence quotient to history learning outcomes in Senior High School 1 Karawang. This research is quantitative type with use experiment design methode treatment by level 2x2. The instrument which used to result of history learning is multiple choices test. Besides, intellegence quotient gets by result of students' IQ test. This test is organized by an institute for IQ test. At that time students' receive in Karawang Senior High School 1. This research's result shows that: (1) result of history learning for students who follows learning model Numbered Heads Together ( NHT) is higer than students who follows conventional learning model. (2) there are interactions between learning model and inttelegence quotient (3) students who follows history learning by use NHT learning model by high intellegence quotient is higer than srudents who follows conventional learning model by high intellegence quotient (4) students' result of history learning who follows NHT learning model bu low intellegence quotient is lower that students' who follows conventional learning method by low intellectual.